Analisis Kesulitan Guru dalam Pembelajaran Matematika di Kelas V Sekolah Dasar Negeri 060967 Medan Belawan - Patresia Situmorang; Rani Anggreani Br Tarigan; Renti Semina Sinaga; Reza Anggreini Br Milala; Yun Parbueuli Munte (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
This research was conducted with the aim of finding out the obstacles or difficulties faced by teachers in teaching mathematics in class V of the state elementary school 060967 Medan Belawan. The type of research used is qualitative research. Researchers collected information by first conducting interviews with research subjects, namely two teachers at SDN.060967 Medan Belawan. Then, after obtaining information regarding the topic of the problem that they want to research, the researcher strengthens the information they find with a literature review. A literature review is a review of books, notes and various reports related to the problem that you want to solve. The obstacles faced in Mathematics learning carried out at SDN.060967 Medan Belawan are how to create learning that increases students' enthusiasm for learning and how to ensure that children do not feel pressured when studying. Students also do not receive full attention from their parents so that learning/tasks are difficult. Given by the teacher was not done well, making the learning tools and how to use the learning tools, the teacher had difficulty connecting the RPP created with the learning media that would be used in class.